Prevalence of GB Virus C/Hepatitis G Virus Infection among Various Populations in Surabaya, Indonesia, and Identification of Novel Groups of Sequence Variants - Handajani, Retno (American Society for Microbiology, 2000)
A molecular epidemiological study was performed to investigate the prevalence of GB virus C/hepatitis G virus (GBV-C/HGV) infection among various populations in Surabaya, Indonesia. The prevalence of GBV-C/HGV RNA, determined by reverse transcription-PCR for a portion of the NS3 region of the viral genome, was 2.7% (4 of 150) among randomly collected blood donor sera, which were all negative for both hepatitis B virus surface antigen and antibodies against hepatitis C virus (HCV). On the other hand, the prevalence among anti-HCV-positive blood donors was 17.8% (13 of 73), with the ratio being significantly higher than that observed with the anti-HCV-negative blood donors (P < 0.001). A high prevalence of GBV-C/HGV infection was also observed among patients with chronic liver disease, such as chronic hepatitis (5.7%), liver cirrhosis (11.5%), and hepatocellular carcinoma (7.0%), and patients on maintenance hemodialysis (29.0%). No correlation was observed between GBV-C/HGV viremia and serum alanine aminotransferase levels in the populations tested, suggesting the possibility that GBV-C/HGV does not cause apparent liver injury. Phylogenetic analysis of sequences of a portion of the 5′ untranslated region and the E1 region of the viral genome identified, in addition to a previously reported then novel group of GBV-C/HGV variants (group 4), another novel group of variants (group 5). This result suggests that GBV-C/HGV can be classified into at least five genetic groups. GBV-C/HGV isolates of group 4 and group 5 were each shown to comprise approximately 40% of the total Indonesian isolates.